New Iron Age funerary data from collective graves in Wādī Fizḥ, northern Oman - Düring, Bleda S.; Olijdam, Eric; Botan, Sam A. (Proceedings of the Seminar for Arabian Studies, 2017)
In the 2016 campaign of the Wādī al-Jīzī Archaeological Project a rich collection of Iron Age funerary artefacts was found from disturbed (probably collective) burials in Wādī Fizh. These graves have relatively few comparanda in eastern Arabia and are therefore of some significance for our understanding of this period. In this paper, we will first discuss the broader Iron Age cultural landscape of Wādī Fizh, and then focus on the cemetery site. We subsequently discuss the pottery, soft-stone vessels, and miscellaneous artefacts retrieved from these grave contexts, and compare our data with those from other sites in Oman and the Emirates.